2020
DOI: 10.1111/mms.12735
|View full text |Cite
|
Sign up to set email alerts
|

Bottlenose dolphins (Tursiops truncatus) in North Dalmatia, Croatia: Occurrence and demographic parameters

Abstract: The common bottlenose dolphin (Tursiops truncatus) population along the eastern Adriatic coast is believed to comprise discrete communities, yet many of them are unstudied. This study provides the first description of occurrence and demographic parameters for the community inhabiting waters of North Dalmatia. Dedicated boat-based surveys conducted in summer months from 2013 to 2017 resulted in 13,896 km of research effort and 284 dolphin sightings from which 336 individuals were identified. Site-fidelity analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…This study provides the first empirical estimates of abundance of bottlenose dolphins at the Tiber River estuary. The overall mark rate ( ) of this population is equal to 0.585, similar to those given by other studies [ 73 , 83 , 84 , 85 , 86 ], with peaks higher than 0.70, as in [ 87 , 88 ]. However, the annual mark rate decreases through the investigated years, with the lowest value in 2020 ( = 0.53).…”
Section: Discussionsupporting
confidence: 88%
“…This study provides the first empirical estimates of abundance of bottlenose dolphins at the Tiber River estuary. The overall mark rate ( ) of this population is equal to 0.585, similar to those given by other studies [ 73 , 83 , 84 , 85 , 86 ], with peaks higher than 0.70, as in [ 87 , 88 ]. However, the annual mark rate decreases through the investigated years, with the lowest value in 2020 ( = 0.53).…”
Section: Discussionsupporting
confidence: 88%
“…Spatial segregation in common and Indo-Pacific bottlenose dolphins has been identified within estuarine systems, embayments, or lagoons [e.g., 7 , 11 , 12 , 82 , 87 , 91 , 93 , 97 100 ], between or among estuarine and coastal groups [e.g., 8 , 14 , 84 , 99 104 ], as well as in coastal open-water areas [ 9 , 94 , 104 ]. The spatial segregation often reflects site fidelity and occurs despite the lack of physical barriers to movements [e.g., 7 , 88 , 94 , 100 , 105 ]. In contrast, some studies have found substantial overlap in core areas [ 15 , 106 ] or no spatial segregation among socially [ 10 , 93 ] or genetically differentiated [ 10 , 107 ] groups.…”
Section: Discussionmentioning
confidence: 99%
“…Possibly counterintuitively, relatedness, alone, has been shown to not explain the strength of social groups [ 8 , 10 , 86 ]. Between groups, geographic distance and overlap in home ranges have positively correlated with association strength [ 88 , 123 ], but not consistently [ 8 , 124 ]. Results from the current study also show higher within-cluster association strength for the Pamlico Sound cluster, most associated with the large estuarine system of Pamlico Sound, although within-cluster association strength was also high in the Beaufort cluster.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study area is an open habitat under the direct influence of the Gulf of Mexico and its oceanographic dynamics. As a general trend, open or oceanic habitats promote wider ranging behavior, resulting in lower site fidelity to certain areas, contrary to complex or closed coastal habitats with temporally and spatially predictable food sources, which promote higher fidelity to relatively small areas (Gowans et al, 2007; Pleslićet al, 2020). In open waters of the northern Gulf of Mexico, Fazioli et al (2006) found that dolphins that prefer open waters of the gulf showed patterns of seasonal residency, extended geographic range out of the study area, or transience, with fewer individuals displaying year‐round residence, contrary to the dolphins that preferred the adjacent inshore areas.…”
Section: Discussionmentioning
confidence: 99%